Awareness of aflatoxin and willingness to pay for aflasafe technology among maize farmers in Cibitoke, Makamba and Bujumbura provinces in Burundi - Nduwimana, D.; Nwenjeri, G.; Bett, E.; Atehnkeng, J. (2024)
This study aimed to assess the awareness of aflatoxin among maize farmers in Burundi and their willingness to pay for Aflasafe technology, with a focus on the provinces of Bujumbura, Cibitoke, and Makamba.